FAKTOR-FAKTOR YANG MEMPENGARUHI IBU HAMIL DALAM MENGIKUTI KEGIATAN KELAS IBU HAMIL DI WILAYAH KERJA PUSKESMAS TANJUNG SENGKUANG TAHUN 2017 - Yuditia Prameswari; Misraini Ali (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Government efforts to accelerate the reduction of Maternal Mortality and Infant Mortality Rate by increasing sufficient knowledge to pregnant women and families through classes of pregnant women. Pregnancy class is a community empowerment activity through shared learning facilities about maternal health, which aims to improve the knowledge and skills of mothers regarding pregnancy. From the data of the Tanjung Sengkuang Community Health Center the target number of pregnant women in 2016 is 1,725 people and those who have attended the class of pregnant women are 41 people (2%) while the government targets here are the Batam City Health Service (100%), ie all pregnant women are expected to be exposed or take classes for pregnant women to reduce maternal mortality and infant mortality. From the above data it can be concluded that there are still a low number of pregnant women to join The Pregnancy Class Activities. The Pregnancy Class Activities is a joint study activity about pregnancy, birth, nifas, BBL, myths, infectious diseases, birth certificate and pregnancy gymnastics and conduct examination of HIV / AIDS test, through practice with KIA book. The purpose of research to determine Factors Affecting Pregnant Women to joining Class Pregnant Women in Work Area TanjungSengkuang Health Center. Research using analytical design with accidental sampling approach. The sample of research is 50 respondents. Data collection with questionnaire and univariate and bivariate data analysis. The results of the study found that there were 42 pregnant women who did not have good knowledge about the class of pregnant women (84%), educated under junior and junior high school as many as 30 people (60%), did not work as many as 34 people (68%), and 39 respondents who have not been exposed to the class of pregnant women (78%).